Highly Sensitive Electrochemical Sensor Based on Zn Porphyrin for Environmental Monitoring of Glyphosate - Rejab, Fatma; Dardouri, Nour Elhouda; Rouis, Ahlem; Echabaane, Mosaab; Jaffrezic‐Renault, Nicole; Halima, Hamdi Ben (Electroanalysis (New York, N.Y.), 2025)
Glyphosate (Gly) is one of the most widely used herbicides in modern agriculture, and its potential risks continue to be a subject of considerable discussion. In this present work, a novel electrochemical sensor was developed using an indium tin oxide (ITO) electrode modified with a zinc (II) metalloporphyrin complex, [5,10,15,20‐tetrayltetrakis(2‐methoxybenzene‐4,1‐diyl) tetraisonicotinateporphyrinato] zinc (II) (ZnTMIPP), for the selective detection of glyphosate. The ZnTMIPP complex was synthesized and thoroughly characterized using UV–vis and FTIR spectrometry, and 1H NMR spectroscopy to confirm its structure and purity. The sensing platform was prepared by drop‐casting the ZnTMIPP onto the surface of a cleaned ITO electrode, forming a uniform and stable film. Electrochemical evaluation of the sensor was performed using cyclic voltammetry under optimized experimental conditions, revealing a sensitive response to glyphosate, with a wide linear detection range from 10–8 to 10–5 M and a low detection limit of 4.14 nM. Furthermore, the modified electrode demonstrated excellent selectivity versus glyphosate metabolite and other pesticides, reproducibility, and stability, highlighting its potential as a cost‐effective and efficient platform for glyphosate monitoring in real water samples and fruit juice. A novel electrochemical sensor is developed, using an indium tin oxide electrode modified with a zinc (II) Metalloporphyrin complex,[5,10,15,20‐terayltetrakis(2‐methoxybenzene‐4,1‐diyl) tetraisonicotinateporphyrinato] zinc(II) (ZnTMIPP), for the selective detection of glyphosate. A sensitive response is obtained with a wide linear detection range from 10‐8 to 10‐5 M and a low detection limit of 4.14 nM.